2005
DOI: 10.1073/pnas.0409120102
|View full text |Cite
|
Sign up to set email alerts
|

Abelson-interactor-1 promotes WAVE2 membrane translocation and Abelson-mediated tyrosine phosphorylation required for WAVE2 activation

Abstract: WAVE2 is a member of the Wiskott-Aldrich syndrome protein family of cytoskeletal regulatory proteins shown to link Rac activation to actin remodeling via induction of Arp 2͞3 activity. WAVE2 is thought to be regulated by its positioning in a macromolecular complex also containing the Abelson-(Abl) interactor-1 (Abi-1) adaptor, but the molecular basis and biologic relevance of WAVE2 inclusion in this complex are ill defined. Here we show that Abi-1 binding to WAVE2 is mediated by discrete motifs in the Abi-1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
248
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(265 citation statements)
references
References 24 publications
16
248
1
Order By: Relevance
“…For example, in leukocytes, Abi1 was found in the WAVE2 complex and Abi2 in WAVE1 complex, whereas both Abi1 and Abi2 were present in WAVE2 complex in A431 cells (20). The basis for specificity of Abi protein incorporation into WAVE1 or WAVE2 complex is not known, although, based on high sequence conservation of binding sites, the affinities of the Abi proteins for WAVE proteins are expected to be similar (20,22,31). One explanation might be that Abi1 and Abi2 exhibit different patterns of threonine and serine phosphorylation (20), which is required for full activation of WAVE2 complex by Rac and acidic phospholipids (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in leukocytes, Abi1 was found in the WAVE2 complex and Abi2 in WAVE1 complex, whereas both Abi1 and Abi2 were present in WAVE2 complex in A431 cells (20). The basis for specificity of Abi protein incorporation into WAVE1 or WAVE2 complex is not known, although, based on high sequence conservation of binding sites, the affinities of the Abi proteins for WAVE proteins are expected to be similar (20,22,31). One explanation might be that Abi1 and Abi2 exhibit different patterns of threonine and serine phosphorylation (20), which is required for full activation of WAVE2 complex by Rac and acidic phospholipids (20).…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 does not interact directly with WAVE but instead binds to the Nap1-binding protein Sra-1 (12) and to Abi1 (21). The Abi1-mediated tyrosine phosphorylation of WAVE2 by Abl regulates WAVE2 complex activity either by regulating conformation of the complex, as suggested (22), or by regulating interactions among the complex components or with other cellular targets (10,23,24). The interaction of Abi1 with p85 (24) might modulate PI3 kinase activity (10); this activity would be consistent with coincident modulation of WAVE complex activity by its interaction with PIP3, or PIP3-mediated membrane recruitment of WAVE2 (25).…”
mentioning
confidence: 99%
“…Westphal and colleagues (32) showed that c-Abl interacts with the WAVE protein complex. Furthermore, c-Abl tyrosine kinase activity was found to be required for the phosphorylation of WAVE2, a close relative of WAVE3 (30). Next, we investigated whether WAVE3 and Abl interact endogenously in MDA-MB-231 cells.…”
Section: Abl Kinase Activity Is Required For Wave3 Tyrosinementioning
confidence: 99%
“…On the other hand, it has been shown that Ablmediated phosphorylation of WAVE2 is mediated by Abi1 in an Abl⅐Abi1⅐WAVE2 complex (30). To test whether Abi1 is required for coupling of Abl to WAVE3 to promote Abl-mediated phosphorylation of WAVE3, we analyzed WAVE3 phosphorylation by Abl both in the presence and absence of Abi1.…”
Section: Abl Kinase Activity Is Required For Wave3 Tyrosinementioning
confidence: 99%
See 1 more Smart Citation